Phytochemical characterization and correlation analysis of nutritional value in sweet pepper (Capsicum annuum L.) genotypes at various growth stages - Bharti, Hemlata; Hemalatha, Nandimandalam; Malita, Rukhsana; Sharma, Vinod Kumar; Bharadwaj, Rakesh; Babu, Prashanth (Frontiers in Plant Science, 2026)
Sweet pepper (Capsicum annuum) is valued globally for its nutritional richness and vibrant colours, with significant commercial and therapeutic potential. This study analysed 49 sweet pepper genotypes (green, red, orange, white, purple, chocolate, yellow) at unripe and mature stages to assess bioactive compounds: vitamin C, total phenols, total soluble sugars, chlorophylls, anthocyanins, carotenoids, and xanthophylls. Results showed considerable variation in vitamin C, ranging from 343.00 (immature) to 12,565.95 µg/g in mature fruits, with promising genotypes CPCT-31A-5 and NBR-22. Antioxidant levels increased from 7.32 (immature) to 431.34 µg/g at maturity, notably in AVR-152, CPCT-32C, and 33B. Total phenols ranged from 146.0 to 6,707.50 µg/g, peaking in mature fruits, especially in AVR-27, NBR-20, F5-32C-3, and Chocolate. Carotenoids and xanthophyll also increased at maturity, with AVR-141 showing the highest content (8.77 µg/g). White capsicum exhibited the highest total soluble solids (43,730.5 µg/g) at the immature stage, while mature orange-red fruits had the richest vitamin C (12,565.95 µg/g) and antioxidants. NBR-10 stood out for chlorophyll content, suggesting potential for photosynthetic studies. Purple capsicum showed the highest anthocyanin content (15.50 µg/g) at the immature stage. Strong correlations were observed between vitamin C and phenols (r = 0.79), antioxidants and vitamin C (r = 0.80), and antioxidants and phenols (r = 0.96) at the immature stage. These findings highlight the dynamic interplay of bioactive compounds across genotypes and maturity stages, with implications for breeding and dietary applications. The study underscores the significant variation in bioactive compounds across sweet pepper genotypes and maturity stages, emphasizing the potential of specific genotypes like CPCT-31A-5, AVR-27, and NBR-10 for enhanced nutritional and breeding outcomes. These insights can guide future research on fruit quality improvement and functional food development.